STOCK MARKET OPENNESS AND MARKET QUALITY: EVIDENCE FROM THE SHANGHAI–HONG KONG STOCK CONNECT PROGRAM. (11th May 2020) - Xu, Ke; Zheng, Xinwei; Pan, Deng; Xing, Li; Zhang, Xuekui
Abstract: We study the impact of capital market openness on high‐frequency market quality in China. The Shanghai–Hong Kong Stock Connect program (SHHKConnect) opens China's stock market to foreign investors and offers a natural experiment to investigate this question. Using a difference‐in‐differences approach, we find that market liberalization leads to lower quoted spread, lower effective spread, lower market depth, and higher short‐term volatility. Our findings imply that opening the markets to more sophisticated foreign investors is associated with higher competition and more cross‐market arbitrage activities, narrowing the spread and reducing liquidity providers' profits, but increasing the price impact and short‐term volatility of connected stocks.